(untitled) (Central Medical College Journal, 2022)
Background: Anthropometric measurements vary in different races, sex and age groups. Estimation of stature is crucial task in the field of forensic medicine and anthropology in identifying the individual especially when body is decomposed, destroyed or certain body parts of unknown remain in mass disasters or from disposed of in gutters or waste dumps. Stature is one of the various parameters of identification. However few studies were conducted using finger lengths for estimation of stature. The purpose of present study to evaluate utility of index and ring finger lengths in estimation of stature. Methods: A cross sectional observational analytical study was conducted on 200 participants where 100 were adult males and 100were females. Ages between 25 to 45 years were selected by convenience sampling technique for the study in the Department of Anatomy of Chittagong Medical College (CMC), Chattogram. Sex differences were tested by using unpaired student’s t-test. Correlations between stature and finger lengths were assessed. Multiplication factors (MF) were calculated for estimating the stature. Results: The present study showed significant (p<0.001) positive correlation between the stature and finger lengths in both genders. We found some multiplication factors which were helpful for estimation of stature from respective measurements. Conclusion: According to result, this study has implication in mass disaster or in criminal cases for nearly accurate estimation of the stature of an unknown individual. Central Medical College Journal Vol 5 No 1 Jan 2021 PP 30-34